Executive Board Progress Report to the IMFC on the Fund's Mandate. (Policy Papers; Policy Paper ;, 2010)
This paper responds to the IMFC call to review, in light of the crisis, the Fund's mandate over macroeconomic and financial sector policies bearing on global stability. The crisis exposed weaknesses in economic oversight-national, regional, and global-prior to the crisis, prompting major institutional innovations to uncover risks and meet large and diverse financing needs. Despite progress, it still needs to be asked if the mandate in the Fund's Articles is up to the challenges ahead. The Board's deliberations, which are far from complete, have prompted it to emphasize practical steps to deliver on the Fund's broad stability mandate, with any need to amend the Articles reconsidered in light of experience. The effectiveness of these steps will also depend on quota and governance reform, as confidence in the Fund as an impartial overseer of global stability and lender of last resort rests on its legitimacy.